Poem of Gondo Arum by Kyai Muhammad Anwar Sanusi Bin Karim: Tracing The Values of Characte - Subaidi Subaidi (Historia Madania: Jurnal Ilmu Sejarah, 2019)
This research explains the values of character building in the poem (sy’ir) of Gondo Arum by Kyai Muhammad Anwar Sanusi bin Karim. This research uses a descriptive qualitative approach. The aim is to explain and analyze a person’s thought, individually or group. The technique of collecting data is done directly by using written document and monumental creature by a person who is a mufti of archipelago, kyai Muhammad Anwar Sanusi bin Karim. Data analysis uses descriptive analysis method. The finding of this research is 1. Respect and well-mannered character. This value is relevant with 9 pillars of national character. In the poem of already explained related with an attitude of talking to parents and others that relate to religious doctrine; 2. The character of honesty is behaviour that is based on the effort of making him/herself as people who always can be trusted in words, action, and work. According to kyai Muhammad Anwar Sanusi bin Karim, honesty is a very admirable character, it is honesty in words and action; 3. The character of hard-working, it means try hard to achieve success and do not know to give up. According to kyai Muhammad Anwar Sanusi bin Karim hard working is described in the poem of by the term of “frequently of study day and night”; 4. Values of love Allah and truthfulness, it means the realization the feeling of relative among human which is Allah creatures is a favor from one and only God, and from the relationship will grow the feeling of loving to each other which is based on piety; 5. The character of a kind and humble, to make a good character person should always try to do good things. The good habit should be done consistently or istiqamah. The good habit will build someone’s character to become good. Any small of goodness always be done then it will be big goodness; 6. The character of coalescence and unity, it means the unity of messed style that is various become one which is intact and harmonious. The implementation of coalescence and unity values is such as defend the compactness, to parents, relative, fellow, and social environment. Keywords: character building, the poem of  Gondo Arum, Islamic literature